Sex bias in rhinology research. Issue 12 (20th July 2018) - Stephenson, Elizabeth D.; Farzal, Zainab; Zanation, Adam M.; Senior, Brent A.
Abstract : Background: Analysis of general surgery literature has revealed noteworthy sex bias and underreporting. Our objective was to determine the prevalence of sex bias and underreporting in rhinology. Methods: All articles in 2016 issues of Rhinology, the American Journal of Rhinology and Allergy ( AJRA ), and the International Forum of Allergy and Rhinology ( IFAR ) were reviewed. Of 369 articles, 248 met inclusion criteria. Excluded studies were cadaveric, meta‐analysis/review, and editorial. Data collected included study type, demographics, and sex‐based statistical analysis. Results: There were 202 clinical and 46 basic science/translational studies. From 188 of 202 clinical studies with known sex, 1 included participants of a single sex. Sex matching >50% (SM50 ) was found in 81.9%, and 55.9% performed sex‐based statistical analysis. Domestic clinical studies performed sex‐based analysis more frequently than international (54.9% vs 44.4%) and exhibited a higher rate of SM50 (84.5% vs 80.3%), though these differences were not statistically significant. For basic/translational studies, 54.5% (24/44) provided sex breakdown. Among these, 29.2% included 1 sex, and 8.3% performed sex‐based analysis. Of 10 using animals, 70.0% utilized 1 sex. The remaining 30.0% did not report sex. None of 4 cell line studies reported cell sex. Less than half (46.2%) of domestic and 56.3% of international studies reported sex breakdown; 7.7% of domestic and 3.0% of international studies performed sex‐based analysis. Conclusion: Although sex may impact outcomes, research without sex reporting and analysis is prevalent, particularly among basic science/translational studies. Future research must account for sex in demographics and analysis to best inform evidence‐based clinical guidelines.